1992
DOI: 10.1677/joe.0.1320093
|View full text |Cite
|
Sign up to set email alerts
|

Preferential release of tri-iodothyronine following stimulation by thyrotrophin or thyrotrophin-releasing hormone in sheep of different ages

Abstract: The influence of TRH and TSH injections on plasma concentrations of tri-iodothyronine (T3) and thyroxine (T4) was investigated in neonatal (injection within 0.5 h after delivery) and growing lambs and in normal, pregnant and lactating adult ewes (all 2 years old and originating from Suffolk, Milksheep and Texal crossbreeds). Neonatal lambs had higher levels of T3, T4 and GH compared with all other groups, whereas prolactin and TSH were higher in lactating ewes. In all animals, injections of TRH increased plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
0
3
1
Order By: Relevance
“…The current study agrees with these obser¬ vations and this suggests that SRIF plays a minor role in the regulation of the basal pulsatile plasma GH profile in the ruminant. The significant GH response to TRH observed in the current study is in contrast to previous observa¬ tions in the sheep (Davis, 1975;Peeters et al 1992). TRH has, however, stimulated GH release from ovine pituitaries in vitro (Takahara et al 191A) and an invivo GH response to a large dose of TRH in the sheep has recently been observed (Spencer et al 1992).…”
Section: Resultscontrasting
confidence: 84%
See 1 more Smart Citation
“…The current study agrees with these obser¬ vations and this suggests that SRIF plays a minor role in the regulation of the basal pulsatile plasma GH profile in the ruminant. The significant GH response to TRH observed in the current study is in contrast to previous observa¬ tions in the sheep (Davis, 1975;Peeters et al 1992). TRH has, however, stimulated GH release from ovine pituitaries in vitro (Takahara et al 191A) and an invivo GH response to a large dose of TRH in the sheep has recently been observed (Spencer et al 1992).…”
Section: Resultscontrasting
confidence: 84%
“…This increase occurred against a trend towards declining plasma T3 observed in all treatment groups. Increased plasma T3 could result from a number of mechanisms including inhibition of T3 degradation, inhibition of T3 excre¬ tion and/or a preferential release of T3 from the thy¬ roid gland in response to TSH (Peeters et al 1992). The timing of the T3 response, as compared with the rapid elevation in T3 following TRH, and the absence of a T4 response suggests that increased plasma T3 could also reflect elevated peripheral conversion of T4 to T3.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the thyroid gland seems unable to respond, in terms of T4 secretion, to a prolonged stimulation by TSH, probably because a depletion of hormonal stores in the gland occurs during the first minutes of life (Slebodzinski, 1972). It is likely that during the first hours of life the thyroid gland can respond to other stimulating factors: small increases of plasma TH followed exogenous prolactin administration in neonatal lamb, but not in growing lambs and ewes (Peeters et al, 1992). Plasma rT3 levels during the first 48 h of life progressively decreased in suckling lambs, but increased in bottle-fed lambs (Cabello and Wrutniak, 1986 and 1990).…”
mentioning
confidence: 99%
“…Plasma TH levels highly correlated with lambs' birth-weight (Dwyer and Morgan, 2006) and were lower in lambs separated from their mothers just after parturition than in those maintained with their mothers (Firat et al, 2005). Neonatal lambs had higher levels of T3 and T4 compared with growing lambs and ewes (Peeters et al, 1992). Growing goat kids displayed higher TH levels than adults (Colavita et al, 1983) and the lowest values were found in elderly animals (Table 1; Lucaroni et al, 1989).…”
mentioning
confidence: 99%